Comparative morphology of the eggs from the eight species in the genus Agathemera Stål (Insecta: Phasmatodea), through phylogenetic comparative method approach - Cubillos, Claudio; Vera, Alejandro (Zootaxa, 2020)
Morphology of Phasmatodea eggs is remarkably diverse and highly valuable in taxonomic research. Two alterative hypotheses have been proposed to describe the phylogenetic relationship of the species from the genus Agathemera Stål. Additionally, descriptions of the egg morphology within Agathemera have been done based on the eggs of two species. This small sample size does not represent the diverse egg morphology along the genus, thus we attempt to describe the eggs from all the known Agathemera species. The main goal of the present study is to determine whether the evolution of the eggs occurred through either divergent or convergent evolution. We based our descriptions on morphometrics, morphology and the ultrastructure. For data analysis, principal component analysis (PCA) was performed on morphometric variables and the characters emerged from the morphological and ultrastructure were mapped over the molecular phylogeny. The results show that it is possible to discriminate among species using the morphology of the different egg structures, and furthermore, a divergent event at the base of the tree, differentiate the overall egg shape and the internal micropylar plate shape. Finally, we conclude that both divergent and convergent evolution are shaping the different structures of the Agathemera eggs.